2021
DOI: 10.3390/su132414050
|View full text |Cite
|
Sign up to set email alerts
|

The Cloud-Enabled Architecture of the Clinical Data Repository in Poland

Abstract: In this article, the authors, using information-systems modeling techniques, and considering current national legal regulations, present the cloud-enabled architecture of a clinical data repository. The patient’s medical record is an important carrier of information necessary for accurate diagnosis and selection of the correct treatment process. Therefore, it is not surprising that since the beginning of the development of computer technologies, databases have been built to enable the management of a patient’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The subject of the case study was a medical system developed for the gathering and archiving of clinical data (Clinical Data Repository-CDR), which serves as a medical data store for many hospital information systems (HIS) deployed according to a multitenant approach. The architecture of this system has been previously outlined in the context of earlier proprietary studies [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject of the case study was a medical system developed for the gathering and archiving of clinical data (Clinical Data Repository-CDR), which serves as a medical data store for many hospital information systems (HIS) deployed according to a multitenant approach. The architecture of this system has been previously outlined in the context of earlier proprietary studies [29].…”
Section: Methodsmentioning
confidence: 99%
“…The system was tested against the flood of critical requests. In the context of the considered cloud-enabled Kubernetes-based CDR system [29], there were requests to create a medical document-a so-called ITI-41 transaction according to the IHE and PIK-HL7 standard.…”
Section: Identifying Pods Involved In Handling Critical Requestsmentioning
confidence: 99%
“…A high throughput NLP architecture was developed in [29] using the clinical text analysis and knowledge extraction system where results obtained showed that the architecture processed 83,867,802 clinical documents in 13.33 days and produced 37,721,886,606 concept unique identifiers (CUIs) across 8 standardized medical vocabularies. A cloud-based architecture was proposed by Augustyn et al [30] and Sarwar et al [31] for Poland and Pakistan, respectively. Here, results showed that the proposed architectures met the set requirements and the criteria of the sustainable development paradigms and could result in the generation of a huge data repository that would help improve patient care, diagnostics and patient outcomes, disease prevention, and disease surveillance of possible outbreaks.…”
Section: Cdr Architectures and Metadatamentioning
confidence: 99%
“…In [29], developed a model that secures the access, storage and protection of using data in cloud-servers in the medical/ hospital sector. The study focused on private clouds and also the public clouds in the Poland based hospitals.…”
Section: Literature Reviewmentioning
confidence: 99%